DAMPAK BUANGAN LUMPUR PANAS PORONG SIDOARJO TERHADAP KUALITAS AIR KALI PORONG - Simon S. Brahmana (JURNAL SUMBER DAYA AIR, 2007)
Since 29 May 2006, hot mud eruption has occured at Porong-Sidoarjo East Java. The impact of hot muderuption is the inundation of the human settlement, school, free way, paddy field and etc. which until 30October 06 has covered an area of about 450 ha. According to the decree of the President on 27 September2006, mud should be discharged into Kali Porong.The chemical and physical characteristics of mud and its water are the high rate of salinity, conductivity, andphenol, with salinity 15.3 29.7; conductivity 33600 - 76600 ?mhos/cm. and concentrations of phenol0.264 20.4 mg/L. The concentration of heavy metals is not too high: cadmium 0.011 0.125 mg/L;chromium hexa valent nd 0.118 mg/L. The BOD and COD of water are 50 -75 mg/L and 100 -150 mg/Lrespectively.The impact of water and mud discharge into the Kali Porong is decrease dissolved oxygen. In the contrary,turbidity, conductivity and salinity will increase dramatically. The concentration of heavy metal as well asphenol showed no change. Before discharge of water, the dissolved oxygen in Kali Porong along thr riverfrom toll bridge to Tanjungsari varied in between 6.0-7.0 mg/L. After discharge of mud water, dissolvedoxygen decrease significantly. In period of 15 to 30 September 2006 dissolved oxygen varied in between 2.7 -6.7 mg/L, from 1 to 30 October 2006 1.0 -4.2 mg/L and from 2 to 26 November 1.0 2.2 mg/L. Theconductivity rate at toll bridge had increased from 5406 ?mhos/cm in September to 9688 in October 2006. Inthe same time salinity had increased from 2.4 to 4.0 ,and turbidity from 98 NTU to 488 NTU.